Reactivity of non-organometallic ruthenium(II) polypyridyl complexes and their application as catalysts for hydride transfer reactions - Chrzanowska, Marta; Katafias, Anna; van Eldik, Rudi (Frontiers in Chemistry, 2023)
Recently, we investigated the substitution behavior of a series of ruthenium(II) complexes of the general formula [RuII(terpy)(N^N)Cl]Cl, where terpy = 2,2':6',2''-terpyridine, N^N = bidentate ligand, in aqueous solutions. We have shown that the most and least reactive complexes of the series are [RuII(terpy)(en)Cl]Cl (en = ethylenediamine) and [RuII(terpy)(phen)Cl]Cl (phen = 1, 10-phenantroline), respectively, as a result of different electronic effects provided by the bidentate spectator chelates. Polypyridyl amine Ru(II) complex, viz. [Ru(terpy)(en)Cl]Cl and [Ru(terpy)(ampy)Cl]Cl (where ampy = 2-(aminomethyl)pyridine), in which the terpy chelate labilizes the metal center, are able to catalyze the conversion of NAD+ to 1,4-NADH using sodium formate as a source of hydride. We showed that this complex can control the [NAD+]/[NADH] ratio and potentially induce reductive stress in living cells, which is accepted as an effective method to kill cancer cells. Polypyridyl Ru(II) complexes, characterized in terms of the behavior in aqueous solutions, can be used as model systems to monitor heterogeneous multiphase ligand substitution reactions at the solid-liquid interface. Colloidal coordination compounds in the submicron range were synthesized from Ru(II)-aqua derivatives of starting chlorido complexes via the anti-solvent procedure and stabilized by a surfactant shell layer.